Effects of elevated atmospheric CO2 on photosynthesis, growth and biomass in Shorea platycarpa F. Heim (Meranti Paya) - Nor Lailatul Wahidah M.; Wan Juliana Wan Ahmad; Nizam M.S.; Che Radziah Che Mohd. Zain. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Elevated atmospheric CO2 is widely reported to stimulate the plant growth and affect plant physiological processes. However, studies on the respond of tropical plant species to elevated CO2 are quite limited and remain largely unknown. The objective of this study was to investigate the effects of elevated atmospheric CO2 treatments on the photosynthetic characteristics, growth and biomass in Shorea platycarpa. Saplings of S. platycarpa were grown for seven months in the open roof gas chamber supplied with elevated CO2 (800±50 μmol mol-1) and in the shade house with ambient CO2 (400±50 μmol mol-1). Measurements of S. platycarpa growth and photosynthetic characteristics were made at frequent intervals. Biomass characteristics were determined using destructive methods after seven months of treatment and nondestructive method was used for leaf area index (LAI) determination. Photosynthetic rate (A) of S. platycarpa was not significantly affected by elevated CO2. Increased water use efficiency (WUE) of S. platycarpa grown in elevated CO2 was due to the reduced stomatal conductance (gs) and transpiration rate (E). The CO2 elevation had no significant effect on the S. platycarpa relative growth rates (RGR) and biomass but significantly reduced the leaf area. A weak correlation was found between photosynthetic rate (A) and relative growth rate (RGR). The results clearly showed that photosynthesis, growth rate and biomass of S. platycarpa were not significantly enhanced by elevated CO2. The findings indicated that elevated CO2 did not affect a relatively slow growing and a late successional peat swamp tree species.